Translation Techniques in Subtitling the March Sisters’ Utterances in Little Women (1994) Movie - Isyana Nurhasanah Oktari; Hero Gunawan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The objective of this research is to find out which types of translation techniques are found in subtitling the main characters’ utterances in Little Women (1994) movie and the reason they are applied in the subtitle. This research used a qualitative method to analyze the subtitles. The data are movie transcripts and Indonesian subtitles that were taken from a movie streaming platform called Netflix. The data is analyzed using Molina and Albir’s theory of translation techniques (2002). The result showed that there are fourteen translation techniques applied in the subtitles namely; Adaptation (0.60%), Borrowing (10.26%), Calque (0.30%), Compensation (19.61%), Discursive creation (1.96%), Establish equivalent (8.45%), Generalization (3.17%), Linguistic amplification (4.07%), Linguistic compression (24.13%), Literal translation (13.12%), Modulation (2.26%), Particularization (1.51%), Reduction (7.99%), and Transposition (2.57%). The dominant type is Linguistic compression technique because subtitles have a character limit per line which forces the translator to compress the sentences into a shorter form.